Effect of heat treatment above the miscibility gap on nanostructure formation due to spinodal decomposition in Fe-52.85 at.%Cr. (15th February 2018) - Xu, Xin; Westraadt, Johan E.; Odqvist, Joakim; Youngs, Tristan G.A.; King, Stephen M.; Hedström, Peter
Abstract: The effect of heat treatment at temperatures above the miscibility gap (MG) on subsequent nanostructure formation due to spinodal decomposition (SD) has been investigated in an Fe-52.85 at.%Cr alloy. In-situ total neutron scattering measurements were conducted above and inside the MG to shed light on the high temperature nanostructure. Thereafter, different quenched-in nanostructures were imposed by heat treatments at various temperatures above the MG, followed by rapid quenching. The effect of the quenched-in nanostructure on subsequent SD was investigated ex-situ by small-angle neutron scattering, analytical transmission electron microscopy and hardness testing. The critical temperature of the miscibility gap was found at ∼580 °C for the Fe-52.85 at.%Cr alloy and below that temperature, phase separation occurs, where the ferrite decomposes into Fe-rich α -phase and Cr-rich α ′-phase. It was found that transient clustering of Cr occurs above the MG and that the tendency of clustering increases with decreasing temperature. The quenched-in clustering present in rapidly quenched materials treated above the MG has a significant effect on the kinetics of SD upon further aging within the MG. It is clear that the significant quenched-in Cr clustering present in samples heat treated at 600 and 700 °C accelerates SD. However, samples heat treated at 1000 °C demonstrate more rapid SD kinetics than samples heat treated at 800 °C. Cr clustering and other mechanisms affecting the kinetics of SD are discussed in the light of the results obtained. Graphical abstract: Image 1